Tourism and regional growth in Europe - Raffaele Paci; Emanuela Marrocu (European Regional Science Association (ERSA), 2013)
The paper aims at analysing the impact of domestic and international tourism on the economic growth process for 179 regions in ten European countries, which are highly representative of total tourism flows. The econometric analysis is carried out for the period 1999-2009 and it is based on a spatial growth regression framework, where the growth rate of GDP per capita at the regional level depends on tourism flows in addition to the traditional production inputs like physical, human and technological capital. Besides controlling for the initial conditions, we also include covariates for geographical, industrial, social and institutional features of the regions. Results, robust to several robustness checks, show the positive effect of domestic and international tourism flows on regional growth.
Keywords: R11; L83; C31; 330; Regional economic growth; Tourism flows; Spatial dependence; Europe